Collaborative Management of Chronic Diseases: The Contribution of Laboratory Specialists and Nursing Technicians in Diabetes Care - Ahmed Salem Aledan; Hajer Abdullah Al Hamdan; Ali Essa Al Nasser; Ahmad Hussain Abosenh; Hussein Hassan Alawad; Dalal Said Aied Alharthi; Mohammed Hajji Alqudaihi; Fatimah Ahmed Aloufi; Norah Mohammed Abdulrahman Alamri; Baqer Hejjimatoq Aljasim (International Journal of Medical Toxicology and Legal Medicine, 2024)
Diabetes mellitus is a leading chronic disease that requires long-term, multifaceted management. While physicians play a central role in patient care, the involvement of other healthcare professionals is essential to achieving optimal patient outcomes. This paper examines the collaborative roles of laboratory specialists and nursing technicians in the management of diabetes. By exploring their contributions, we aim to highlight how these roles improve patient education, monitoring, and disease management. We argue that an integrated, team-based approach, where laboratory specialists provide diagnostic and monitoring support, and nursing technicians contribute to patient education, lifestyle modification, and hands-on care, leads to better outcomes in diabetes management. The paper also discusses the potential barriers to effective collaboration and offers recommendations for enhancing interprofessional communication and teamwork in diabetes care.